Program Kemitraan Masyarakat Melalui Stimulasi Tumbuh Kembang Anak Usia Pra Sekolah Di Tk Dharma Wanita Desa Ngadisuko Kecamatan Durenan Kabupaten Trenggalek - Wulandari, Dewi; Ixora, Ixora (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2024)
Children's social development begins to become somewhat complex when children reach the age of 3 years, because children have begun to enter the most basic realm of education, namely kindergarten. Children's social development is obtained from maturity and learning opportunities from various environmental responses to children. Early childhood education is a form of effort to stimulate pre-school social development (Fajarwati, et al, 2020). A child's development is influenced by various factors which influence each other, including: the stimulation the child receives from infancy, the maturity of the child when receiving the stimulation, the innate characteristics of the child, the attitude of the parents towards the child or baby and the interaction between the parents and the child. . Developmental stimulation has never been carried out at the Dharma Kindergarten, Ngadisuko Village, Durenan District. Early childhood really needs developmental stimulation to achieve optimal growth and development. Therefore, activities to stimulate children's mental growth and development through therapeutic group therapy are deemed necessary to improve children's mental growth and development. Implementation of stimulation of children's mental growth and development through therapeutic group therapy. Based on this description, the service team will carry out Community Service regarding the stimulation of early childhood growth and development at the Dharma Wanita Kindergarten, Ngadisuko Village, Durenan District, Trenggalek Regency